Jane Fonda at Watkins' Home re Campaign for Economic Democracy Fundraiser - Watkins, Howard::::::::: (1982)
Jane Fonda at microphone speaking to group; Kathy Reilley by back pillar, JV Henry in white top, Carol Bequette in white outfit